Pengaruh Independensi dan Etika Auditor terhadap Kualitas Audit Pada Kantor Akuntan Publik di Jakarta Selatan - Sukma Benga Ola; Rudi Ginting; Wati Rosmawati (Akuntansi, 2025)
The purpose of this study is to find empirical evidence about the influence of audior identity and ethics on audit quality from public accounting firms in South Jakarta. Data collection was carried out through questionnaires distributed to auditors as many as 60 questionnaires, the number of questionnaires that returned 60 questionnaires, the data analysis method used was multiple regression analysis where the influence of auditor independence and ethics on audit quality was a variable Independence while audit quality is a dependent variable. The results of this study show that the influence of auditor independence and ethics on audit quality has a significant effect on audit quality. The results of the t-test showed that the significant value of the independence variable was (0.2542), the auditor ethics variable was (0.2542) and the auditor ethics variable (0,2542).